Within and Beyond the Community: Tensions in Muslim Service Provision in Switzerland - Noemi Trucco; Hansjörg Schmid; Amir Sheikhzadegan (Religions, 2023)
Muslim religious professionals are caught between the expectations of the community they serve and belong to and the expectations of the society they live in. Drawing on Helmut Plessner’s notion of “antithetical tensions between community and society”, this study addresses questions of how Muslim religious professionals experience these tensions and how they cope with them. The data presented are based on semi-structured interviews conducted as part of exploratory research on Muslim service providers in the Canton of Zurich, Switzerland. The findings show that Muslim religious professionals have to deal with community-related challenges such as generational differences, social change and fragmentation, together with outside influences including radicalisation and challenges related to society. Given the recurrent debates on Islamic radicalisation and terrorism in media and politics, they are expected to prove they are peaceful and loyal citizens, even though they are more often than not accused of not being integrated into society. Muslim religious professionals work strenuously, often on a voluntary basis, to do justice to expectations from both sides and try to be non-provocative by engaging in low-profile activities. Finally, they reach out to the wider society, e.g., by participating in inter-religious dialogue and, therefore, engage in bridging activities.